Building organizational compassion among teams delivering end-of-life care in the intensive care unit: The 3 Wishes Project. (October 2020) - Vanstone, Meredith; Sadik, Marina; Smith, Orla; Neville, Thanh H; LeBlanc, Allana; Boyle, Anne; Clarke, France J; Swinton, Marilyn E; Takaoka, Alyson; Toledo, Feli; Baker, Andrew J; Phung, Peter; et al.
Background: The 3 Wishes Project is a semistructured program that improves the quality of care for patients dying in the intensive care unit by eliciting and implementing wishes. This simple intervention honors the legacy of patients and eases family grief, forging human connections between family members and clinicians. Aim: To examine how the 3 Wishes Project enables collective patterns of compassion between patients, families, clinicians, and managerial leaders in the intensive care unit. Design: Using a qualitative descriptive approach, interviews and focus groups were used to collect data from family members of dying patients, clinicians, and institutional leaders. Unconstrained directed qualitative content analysis was performed using Organizational Compassion as the analytic framework. Setting/participants: Four North American intensive care units, participants were 74 family members of dying patients, 72 frontline clinicians, and 20 managerial leaders. Results: The policies and processes of the 3 Wishes Project exemplify organizational compassion by supporting individuals in the intensive care unit to collectively notice, feel, and respond to suffering. As an intervention that enables and empowers clinicians to engage in acts of kindness to enhance end-of-life care, the 3 Wishes Project is particularly well situated to encourage collective responses to suffering and promote compassion between patients, family members, and clinicians. Conclusions: Examining the 3 Wishes Project through the lens of organizational compassion reveals the potential of this program to cultivate the capacity for people to collectively notice, feel, and respond to suffering. Our data document multidirectional demonstrations of compassion between clinicians and family members, forging the type of human connections that may foster resilience.